Profil Literasi Budaya Siswa Madrasah Ibtidaiyah Dalam Konteks Cerita Rakyat, Tari Tradisional, Ritual Adat Di Maluku Utara. - Irwan, Risma; Asep, Putri Handayani; Mansur, Indriyani; Lukmana, Dana Arif; Jaohar, Yuliani (Peneliti.net, 2023)
Social and cultural literacy is the ability to understand and practice the prevailing values within a society, which distinguish it as unique. Cultural and civic literacy play a crucial role in preserving and developing the local and national cultures present in a society. Cultural literacy is not limited to schools and communities; it also contributes to building the identity of the Indonesian society. Furthermore, cultural and civic literacy are particularly vital in the 21st century and during the Industrial Revolution era in Indonesia, considering the diverse ethnic, linguistic, religious, and social status groups. Maluku Utara is one of the provinces in Indonesia, comprising 8 districts and cities with its capital located in Sofifi. It bears the motto